Leptospirosis Transmission in Ponorogo District of East Java, Indonesia - Corie Indria Prasasti; Aditya Sukma Pawitra; Khuliyah Candraning Diyanah; Moch Irfan Hadi; M. Yusuf Alamudi (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aims to identify Leptospira bacterial infection in livestock owners and their livestock, as well as to examine potential risk factors correlated with the incidence. 50 participants were selected and their blood samples were collected. 50 urine samples were collected from livestock owned by the participants. Polymerase Chain Reaction (PCR) was used to identify the existence of the Leptospira bacteria. The questionnaire instrument was used to obtain information about individual characteristics and hygiene. The Chi-Squared test was adopted to examine the correlation between outcome and explanatory variables. The confirmation PCR test detected the bacterial DNA in 2 out of 50 blood samples examined (4%) and 3 out of 50 urine samples examined (6%). Human leptospirosis incidence is significantly correlated with occupation type (p=0.035), personal protective equipment (PPE) use (p=0.044), water puddle contact (p=0.044), cage sanitation (p=0.044) and Leptospira bacteria presence in livestock urine (p=0.007). Insignificant correlation was showed in owners’ age variable. The presence of Leptospira bacteria both in livestock and the owners indicates the real threat of animal to human transmission. Further study with larger sample size and wider range variables and meticulous examination technique is required to comprehend the investigation.